Neuroendocrine Mechanisms for Immune System Regulation During Stress in Fish - Imarai-Bahamonde, C; Montoya-Kunsting, M; Acuna-Castillo, C; Jara-Picas, P; Valenzuela-Montenegro, B (2014)
In the last years, the aquaculture crops have experienced an explosive and intensive growth, because of the high demand for protein. This growth has increased fish susceptibility to diseases and subsequent death. The constant biotic and abiotic changes experienced by fish species in culture are challenges that induce physiological, endocrine and immunological responses. These changes mitigate stress effects at the cellular level to maintain homeostasis. The effects of stress on the immune system have been studied for many years. While acute stress can have beneficial effects, chronic stress inhibits the immune response in mammals and teleost fish. In response to stress, a signaling cascade is triggered by the activation of neural circuits in the central nervous system because the hypothalamus is the central modulator of stress. This leads to the production of catecholamines, corticosteroid-releasing hormone, adrenocorticotropic hormone and glucocorticoids, which are the essential neuroendocrine mediators for this activation. Because stress situations are energetically demanding, the neuroendocrine signals are involved in metabolic support and will suppress the "less important" immune function. Understanding the cellular mechanisms of the neuroendocrine regulation of immunity in fish will allow the development of new pharmaceutical strategies and therapeutics for the prevention and treatment of diseases triggered by stress at all stages of fish cultures for commercial production. © 2014 Elsevier Ltd.